2021
DOI: 10.3390/s21165544
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of the Pulse Rate Variability Analysis Module of a Photoplethysmography-Based Telemedicine System

Abstract: Alterations of heart rate variability (HRV) are associated with various (patho)physiological conditions; therefore, HRV analysis has the potential to become a useful diagnostic module of wearable/telemedical devices to support remote cardiovascular/autonomic monitoring. Continuous pulse recordings obtained by photoplethysmography (PPG) can yield pulse rate variability (PRV) indices similar to HRV parameters; however, it is debated whether PRV/HRV parameters are interchangeable. In this study, we assessed the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 81 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Given the more reliable normative data available for nonlinear-domain metrics and their superior reliability in PPG measurements, using SD1% and SD2% is the better choice. 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the more reliable normative data available for nonlinear-domain metrics and their superior reliability in PPG measurements, using SD1% and SD2% is the better choice. 27 …”
Section: Resultsmentioning
confidence: 99%
“…and Antali et al ., most metrics are omitted due to redundancy or due to evidence of them being prone to artifacts, or artificial noise, leaving SDNN, SD1, and SD2 as metrics for evaluation. 26 , 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart rate variability, determined based on the use of PPG signals, is a relatively little studied method, and at the same time, PPG sensors are convincingly entering the everyday life of modern people. The authors of [ 18 ] studied PPG records of patients diagnosed with diabetes using HRV parameters in the time and frequency range. Publication [ 19 ] examined healthy young and adult individuals using HRV analysis of PPG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Most research groups that acquire cardiac signals in brain imaging studies use the finger pulse instead of ECGs, as revealed by a mega-analysis of neuroimaging data from an international community [8]. Several studies suggested that the pulse rate can be used as an accurate surrogate for the heart rate [21][22][23]. A meta-analysis by Schäfer and Vagedes (2013) concluded on the 'sufficient accuracy' of HRV derived from the finger pulse, especially during the resting condition [24].…”
Section: Introductionmentioning
confidence: 99%